Effects of light irradiation on essential oil biosynthesis in the medicinal plant Asarum heterotropoides Fr. Schmidt var. mandshuricum (Maxim) Kitag - Wang, Zhiqing (PLoS One, 2020)
Asarum heterotropoides Fr. var. mandshuricum (Maxim) Kitag (Chinese wild ginger) is an important medicinal herb. Essential oil extracted from its roots is the key ingredient and is mainly composed of phenylpropanoid compounds. As a skiophyte plant, light is a crucial factor for A. heterotropoides var. mandshuricum growth and metabolism. To investigate the effects of light irradiation on the essential oil biosynthesis in A. heterotropoides var. mandshuricum, the plants were cultivated in four light irradiation treatments (100, 50, 24 and 12% full sunlight). The photosynthetic capacity, essential oil content and composition, activities of several enzymes and levels of some secondary metabolites involved in the shikimic acid and cinnamic acid pathways were analyzed. The leaf mass per area, average diurnal net photosynthetic rate, and the essential oil content increased significantly with increasing light intensity. Phenylalanine, cinnamic acid, and p-coumaric acid in the cinnamic acid pathway were at their highest levels in plants cultivated in 100% full sunlight. The highest content of shikimic acid in the shikimic acid pathway was obtained in plants grown in 50% sunlight transmittance. The activity of the enzymes 3-Deoxy-D-arabino-heptulosonate-7-phosphate synthase, phenylalanine ammonia lyase, cinnamate-4-hydroxylase and 4-coumarate:CoA ligase increased proportionally with light intensity. Overall, we conclude that high light irradiation promotes high net photosynthetic rate, high activity of enzymes and high amounts of phenylpropanoid precursor metabolites leading to significant biosynthesis of essential oil in A. heterotropoides var. mandshuricum.